Modulation of immune responses by Plasmodium falciparum infection in asymptomatic children living in the endemic region of Mbita, western Kenya. Issue 3 (June 2018) - Kijogi, Caroline; Kimura, Daisuke; Bao, Lam Quoc; Nakamura, Risa; Chadeka, Evans Asena; Cheruiyot, Ngetich Benard; Bahati, Felix; Yahata, Kazuhide; Kaneko, Osamu; Njenga, Sammy M.; Ichinose, Yoshio; Hamano, Shinjiro; et al.
Abstract: Individuals living in malaria endemic areas become clinically immune after multiple re-infections over time and remain infected without apparent symptoms. However, it is unclear why a long period is required to gain clinical immunity to malaria, and how such immunity is maintained. Although malaria infection is reported to induce inhibition of immune responses, studies on asymptomatic individuals living in endemic regions of malaria are relatively scarce. We conducted a cross-sectional study of immune responses in asymptomatic school children aged 4–16 years living in an area where Plasmodium falciparum and Schistosoma mansoni infections are co-endemic in Kenya. Peripheral blood mononuclear cells were subjected to flow cytometric analysis and cultured to determine proliferative responses and cytokine production. The proportions of cellular subsets in children positive for P. falciparum infection at the level of microscopy were comparable to the negative children, except for a reduction in central memory-phenotype CD8 + T cells and natural killer cells. In functional studies, the production of cytokines by peripheral blood mononuclear cells in response to P. falciparum crude antigens exhibited strong heterogeneity among children. In addition, production of IL-2 in response to anti-CD3 and anti-CD28 monoclonal antibodies was significantly reduced in P. falciparum -positive children as compared to -negative children, suggesting a state of unresponsiveness. These data suggest that the quality of T cell immune responses is heterogeneous among asymptomatic children living in the endemic region of P. falciparum, and that the responses are generally suppressed by active infection with Plasmodium parasites. Highlights: We tested immune response in Plasmodium positive or negative asymptomatic children. We found modulation of T cell function and NK number in parasite positive children. Immune responses are generally suppressed by active P. falciparum infection. Quality of T-cell immune responses to P. falciparum antigens is heterogeneous.